Kajian Perubahan Penggunaan Lahan Kawasan Perumahan Nasional di Kecamatan Medan Helvetia - Rima Purnala Rosyi; Anthoni Veery Mardianta (TATALOKA, 2021)
Perum Perumnas which was formed by the Central Government in providing housing for low-income groups of people, made a design with a uniform minimum standard, which in the end the house in a certain period of time will experience changes made by residents. Both the house and the perumnas environment will continue to experience changes every year, this is due to the increasing number of population and the alternation of residents in the perumnas. To find out what changes have occurred in Perumnas Helvetia, data processing and analysis is carried out descriptively and using cross tabulation (crosstab). The results of data processing and analysis show that the building area is the change most often carried out by the occupants of the house. For the area of land / land there is no change. The type of house also affects changes in building area, which means that where the building area changes, the type of house will also change. As for other perumnas environments, roads are the changes that have changed the most in perumnas, ranging from width to pavement.change in the residential enviroment, national housing